Rural–Urban Differences in Mild Cognitive Impairment Among Patients with Chronic Obstructive Pulmonary Disease in ChengDu, China - Chen, Xiaomei; Dong, Xunhu; Liu, Jia; Liu, Xiao; Deng, Menghui; Yang, Yanni (International journal of chronic obstructive pulmonary disease, 2023)
Purpose: The rural-urban gap in sociodemographic, lifestyle, and disease-related characteristics among COPD patients is prevalent. These differences may influence the prevalence of mild cognitive impairment (MCI). This study aimed to compare the prevalence and determinants of MCI between rural and urban areas among COPD patients. Patients and Methods: The cross-sectional study sample comprised 372 COPD patients from China. We evaluated the cognitive function and lung function, collected sociodemographic, lifestyle, and disease-related information, to compare the prevalence of MCI in rural and urban areas. Using multivariate regression analysis to examine the effects of variables to MCI. Results: The prevalence of MCI in rural areas was higher than that in urban areas (65.4% vs 47.9%, P=0.001). The prevalence in farm laborers was almost twice as high as that of non-farm laborers in urban areas (82.6% vs 43.1%), but no significant difference in rural areas (P=0.066). However, the data were lower in subjects who insisted on long-term home oxygen therapy (39.7%, CI:27.8-51.6, P<0.001), and who with higher monthly household income (49.6%, CI:40.2-58.9) in rural areas, but no significant difference in urban areas (P=0.985 and 0.502). Multivariate logistic regression analysis indicated that participants aged 71 years and above, former smokers were at a high risk of MCI in both urban and rural areas. However, participants who slept for 6-8 hours a day, shopping frequently, or exercised for more than 2 hours a day had a lower risk of MCI in urban areas. But rural participants who insisted on long-term home oxygen therapy had a lower probability of developing MCI. Conclusion: This study revealed that there were significant differences in MCI among COPD patients in rural and urban areas, especially in exercise, sleeping, shopping, and long-term home oxygen therapy. Medical staff should give health guidance according to the actual situation of patients with COPD. Keywords: chronic obstructive pulmonary disease, mild cognitive impairment, urban, rural